Pembuatan Website Wisata Desa Gajahrejo Dalam Meningkatkan Daya Saing Sebagai Desa Wisata Sekaligus Memasarkan Produk Unggulan Desa - Dediek Tri Kurniawan; Arum Prasasti; Raisa Fitri; Inanda Shinta Anugrahani; Yesiana Ihda Kusnayain (Indonesian Journal Publisher, 2020)
Indonesia is a country with good economic growth, one of the main contributors of gross domestic product (GDP) is the tourism sector. The country's foreign exchange receipts from the sector continued to grow to US 16.11 Billion in 2018. The existence of tourist villages is now a concern of the government in increasing economic equality and reducing the Gini ratio from Indonesia. The potential of tourist villages is huge, about 1,734 potential tourist villages that have the potential to be developed salag the only one is Gajahrejo village located south of malang regency. Gajahrejo village has tremendous economic potential with its wealth and superior products. So, the creation of a website is one of the solutions to the economic improvement of Gajahrejo village. By using waterfall method in the development process that begins with analysis until maintenance is able to provide outstanding website results, by going through 3 stages namely preparation, implementation, and evaluation. With the process and methods used produced a website that serves as a data center and the sale of products from Gajahrejo village as an effort to strengthen the branding of the village.